The effect of Participatory decision making on organizational performance with morals, knowledge and attitude as mediation variables - Netty Laura; Putri Nasution (Institute of Computer Science (IOCS), 2022)
Organizational performance is a standard benchmark for a company to continue to innovate to achieve company goals. This study examines the effect of participatory decision making on organizational performance with ethical leadership as a mediating variable. The sampling technique used the Random Sampling method with a total data of 100 respondents who are employees of private companies located in Jakarta using partial least squares (PLS) data analysis. Finally, from this research, it can be seen that participatory decision-making significantly affects morals, attitudes, and knowledge. Then, morals and knowledge have a significant effect on organizational performance. Meanwhile, the attitude has no significant effect on organizational performance. And for the mediating variable, it is known that morals and knowledge are significant in mediating participatory decision making with organizational performance.